Mahkamah Konstitusi dalam Perjalanan Reformasi Birokrasi - Ibrahim, Siti Noor Khatija; Rahmawati, Rosyida; Rudiatin, Endang (Asosiasi Ahli Administrasi Indonesia, 2024)
The purpose of this study is to analyze the bureaucratic ethics of the Constitutional Court related to the objectives and constitutional values in the decisions of the Constitutional Court judges, as well as the role of bureaucratic reform based on Presidential Regulation Number 81 of 2010. The method used is a literature study. This method involves analyzing secondary data from Constitutional Court decisions, laws and regulations, and other scientific literature focusing on the research topic. The results showed that ethical violations by Constitutional Court judges are a serious challenge to the integrity of the Constitutional Court institution. After the amendment of the 1945 Constitution after the reform, the Constitutional Court became the highest judicial institution against corruption, collusion, and nepotism. Despite four amendments, legal irregularities in the Constitutional Court still occur, indicating that post-reform law enforcement has not been optimal. The main challenge is the inability of the bureaucracy to serve the public interest. The importance of bureaucratic reform is illustrated by the need to improve the integrity of the Constitutional Court, rebuild public trust, and ensure that this institution continues to function as a justice enforcer that serves the public interest.